DESIGN OF EMBANKMENT FOR AIRSIDE FACILITIES AND SUBSTRUCTURE OF PASSANGERâS TERMINAL ADI SOEMARMO AIRPORT, SURAKARTA - Yoga Pratama Jubaedi, Dimas
Adi Soemarmo Airport is one of the international airports located in Surakarta, Central Java. This airport is operated for domestic flights and overseas flights. Recent passenger trend shows increasing in demand and this airport has to accomodate it. The easiest way to overcome the issues is to increase the capacity of its airside and landside facilities. The development cause the airport needs the design of embankment for airside facilities and subsctructure for passanger’s terminal. All of the design works adhere to the national standard code SNI 8460:2017 about geotechnical design. Airside facilities of Adi Soemarmo Airport needs 1,5 meter of embankment for raising the elevation to avoid the airport pavements close to the ground water table. The considerations for embankment design are the strength of its bearing capacity and the serviceability which can be seen from the total settlements of embankment. In this occasion, the bearing capacity and settlement of embankment is modeled as occured in shallow foundation. Its bearing capacity will be determined by using Terzaghi equation while the settlement will be counted based on elasticity and consolidation theory. The passanger’s terminal is designed using concrete structure with SRPMK system (Special Moment Resisting Frame System). Through the modeling application (SAP2000), there will be a design for deep foundation, pile cap, and tie beam. All of the components will work together to hold the upper structure of the passanger’s terminal. The deep foundation which selected is bored pile with depth of penetration up to 18 meter below the ground and has two types of diameter, 400 mm and 500 mm. It requires adequate bearing capacity to hold the ultimate working load. The load combination based on SNI 1727:2013, where the ASD concept is used for deformation analysis and the LRFD concept is used for detailing the subsctructure. At the top of pile, it connects to the pile cap measuring 2100x2100 and 2500x2500. To solve differential settlement issues, each pile cap will be connected using 700x350 tie beam. Futhermore, all the design processes are aided by using geotechnical software, such as L-PILE and GROUP PILE.